Gratitude Can Help Women At-Risk for Depression Accept Their Depressive Symptoms, Which Leads to Improved Mental Health - Tomczyk, Joanna; Nezlek, John B.; Krejtz, Izabela (Frontiers in Psychology, 2022)
Introduction: Dispositional gratitude is an orientation that includes being grateful for the positive aspects of one’s life and an appreciation of altruistic gifts. A growing body of research suggests that gratitude is positively related to well-being and psychological adjustment. The present study examined the extent to which acceptance of illness – a measure of adjustment to a distressing condition - mediated relationships between gratitude and well-being among women who had elevated levels of depressive symptoms. Methods: Participants were 131 women who, based on scores on the Center for Epidemiological Studies Depression scale, were at risk for experiencing clinical depression. Thirty-five of these participants had been diagnosed as depressed at some point in their lives and ninety-six had not. Participants completed measures of gratitude, well-being, anxiety, and acceptance of illness. Results: Dispositional gratitude was positively correlated with well-being and was negatively correlated with depression and anxiety. Dispositional gratitude was also positively correlated with acceptance of illness. Mediational analyses found that acceptance of illness mediated relationships between gratitude and well-being, between gratitude and anxiety, and between gratitude and depression. Moreover, such mediation varied as a function of whether women had ever been diagnosed as depressed. Acceptance of illness was related more strongly to well-being for women who had been diagnosed as depressed at some time in their lives than it was for women who had never been diagnosed as depressed. Conclusion: Women with elevated depressive symptoms who were more grateful (compared to those who were less grateful) were more accepting of their condition, which was related to increased well-being and decreased feelings of depression and anxiety.